Genetic Study of Cerebral Small Vessel Disease in Chinese Han Population - Wang, Yunchao; Shi, Changhe; Li, Yusheng; Yu, Wenkai; Wei, Sen; Fan, Yu; Mao, Chengyuan; Yang, Zhihua; Yu, Lulu; Zhao, Zichen; Li, Shanshan; Gao, Yuan; et al. (Frontiers in Neurology, 2022)
Cerebral small vessel disease (CSVD) is a syndrome of clinical, neuroimaging, and neuropathological manifestations caused by disorders that affect small cerebral vessels. Although the pathogenesis of the disease remains unclear, some studies have demonstrated that genetic variants contribute to the development of CSVD. Our study aimed to explore the genetic characteristics of CSVD in the Chinese Han population. We enrolled 182 sporadic CSVD Chinese Han patients whose magnetic resonance imaging results showed grade 2-3 white matter lesions. Target region sequencing of seven monogenic CSVD-related genes, including NOTCH3, HTRA1, COL4A1, COL4A2, GLA, TREX1, and CTSA, was performed, and we identified pathogenic variants by screening the sequencing results and functional predictive analysis. All variants were predicted to be pathogenic by the SIFT Score, Polymorphism Phenotyping-2 score, Mutation Taster, Splice site score calculation, and MaxEntScan. All variants were validated in 300 healthy controls. In total, eight variants were identified in patients with CSVD, including five novel variants, c.1774C>T (NOTCH3), c.3784C>T (NOTCH3), c. 1207C>T (HTRA1), and c. 1274+1G> A (HTRA1), c.1937G>C (COL4A1) and three reported mutations. None of these variants were present in 300 healthy controls. No pathogenic variants in COL4A2, GLA, TREX1, and CTSA were detected. This study identified five novel variants in CSVD-related genes in Chinese Han patients with sporadic CSVD. Our results expand the genetic profile of CSVD.